Correlation Individual Characteristics and Work Stress with Menstrual Disorders in Tobacco Farmers - Indriyanti Indriyanti; Tri Martiana; Firman Suryadi Rahman (Universitas Airlangga, 2019)
Introduction: Women participation at work, especially in the agricultural sector, is implies a status of gender equality that positions women as capable of doing work like men. However, women naturally have physically and biologically differenced with men, for example in reproductive health conditions. Menstrual disorders are important to know because it can show the function of women reproductive health disorder. Menstrual disorders can be caused by various factors. The purpose of this study was to identify individual characteristics and psychological factor (work stress) with menstrual disorders of female tobacco farmers in Ambulu Village, Jember City. Methods: This study was an observational analytic with a cross-sectional approach. The research was conducted on August 2018 and respondents were 36 female tobacco farmers chosen by simple random sampling. Dependent variable of this study was menstrual disorders and the independent variables were individual characteristics (age, marital status, and work period) and psychological factor (work stress). Results: Obtained were that most of the respondents aged 35-44 years (55.6%), married (91.7%), having work period over 5 years (69.4%) and 58.3% respondents experienced a moderate level of work stress. Conclusion: There was a relationship between work stress and menstrual disorders. There was no relationship between individual characteristics with menstrual disorders in tobacco farmers in Ambulu Village, Jember City. Keywords: individual characteristics, menstrual disorders, work stress